Baking Effect on Resistant Starch Digestion from Composite Bread Produced with Partial Wheat Flour Substitution - Rafael Grassi de Alcântara; Heidge Fukumasu; Paulo Cesar Fabricio Raspantini; Leonila Ester Reinert Raspantini; Caroline Joy Steel; Ludmilla de Carvalho Oliveira; Rosemary Aparecida de Carvalho; Fernanda Maria Vanin (Journal of Food Quality)
The consumption of composite flour, such as green banana and corn flour, is related to maintain stable blood glucose levels, due to high resistant starch levels. However, most of these studies have conducted analyses of unprocessed food such as flour. Therefore, this study aimed to evaluate the effect of baking on resistant starch concentration and digestion from bread produced with partial wheat flour substitution. Response surface methodology was used to evaluate bread physical-chemical characteristics, and then, sensorial and nutritional qualities of the bread were evaluated. The feasibility of incorporating 40% of corn flour was demonstrated, while incorporation of 20% produced bread with similar characteristics to the control; for green banana flour, these levels were 20 and 10%, respectively. Resistant starch levels of composite breads were also enhanced by in vitro analyses. On the other hand, in vivo blood glucose levels evidenced that the ingestion of breads produced with partial wheat flour substitution by green banana or corn flour promoted a more important peak in blood glucose levels in comparison with control bread, which was never previously presented in the literature. Bread ingestion rapidly increased the blood glucose levels of rats; once during the baking process, starch granules become gelatinized and therefore easily digestible. Furthermore, this study also highlighted the lack and need for future investigation of wheat flour-substituted baked goods, in order to better understand mechanical properties formation and also product digestibility.